Aging and work: perceptions and experiences of higher education teachers at maturity - Freitas, Milena Cristina de; Gil, Claudia Aranha (Universidade Estadual de Campinas, 2019)
This study presents results of a research that aimed to understand the conceptions of higher education teachers in maturity about the relationship of aging and work. A descriptive study with a qualitative approach was carried out with 10 university professors from the state of São Paulo. Data analysis was based on the multiple case study technique. It was observed that teachers associated different perceptions of aging linked to losses and gains. They demonstrated the teaching work related to pleasure and the possibility of contributing to a better society. It is concluded that it is necessary to expand the theme in new research